Sublimation, art and void. An approach to Aesthetics from the articulation between Philosophy and Psychoanalysis (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
This article constitutes a contribution to the knowledge of art in its connection with philosophy and psychoanalysis, as it approaches to the tension between the representation and the symbolic construction of the artistic image in the contemporary cultural / aesthetic context, through the relationship between the Lacanian Real and Adorno's negative aesthetic. This relationship finds its articulation point in the aesthetic phenomenon of the Beautiful, understood as what confronts the subject with the emptiness of its radical desire, without deceiving it and that allows to integrate the Real´s negativity with the formal elements that make up the artistic work, as well as the Adornian proposal concepts of radicality and authenticity. At the end, a psychoanalytic interpretation of colombian artist Doris Salcedo’s work is made, in which the negative aesthetics and the aesthetic effect of the Beautiful are integrated.
Keywords: Philosophy; psychoanalysis; sublimation; art; aesthetics